Assessment of the transmission of live-attenuated chikungunya virus vaccine VLA1553 by Aedes albopictus mosquitoes - Andrea Fritzer; Andreas Suhrbier; Leon E. Hugo; Bing Tang; Greg Devine; Sandra Jost; Andreas L. Meinke (Parasites & Vectors)
Abstract Background Chikungunya virus (CHIKV) is a mosquito-transmitted, arthritogenic alphavirus that causes sporadic outbreaks of often debilitating rheumatic disease. The recently approved CHIKV vaccine, IXCHIQ, is based on a live-attenuated CHIKV strain (VLA1553), with viraemic vaccine recipients theoretically able to transmit VLA1553 to mosquitoes with ensuing onward transmission. We thus evaluated VLA1553 transmission from artificial blood meals to Aedes albopictus mosquitoes, and onward transmission to mice. Methods Female A. albopictus mosquitoes were fed on defibrinated sheep blood containing wild-type CHIKV (viral titre: 7.50 log10CCID50/mL) or VLA1553 (viral titres: 7.85, 5.72, 4.58, and 3.79 log10CCID50/mL). Viral titres in mosquito bodies and saliva were determined using CCID50 assays 7–8 days after the blood meal. After providing CHIKV or VLA1553 (viral titres ~ 7–8 log10CCID50/mL) in blood meals to mosquitoes, infected mosquitoes were fed on highly susceptible Irf3/7 −/− mice (n = 3 per group). Data were re-analysed using the same reverse transcription quantitative polymerase chain reaction (RT-qPCR) as for an earlier VLA1553 phase 1 clinical trial, to allow correlations between blood meal titres and viraemia in vaccine recipients. Results Mosquito body viral titres were significantly higher (P < 0.0001) for CHIKV versus VLA1553-fed mosquitoes at blood meal viral titres of ~ 7–8 log10CCID50/mL. Mosquito body VLA1553 titres decreased with reducing blood meal titres, but there was no dose-dependent effect on saliva viral titres. No dissemination to salivary glands was seen at blood meal titres ≤ 3.875 log10CCID50/mL. CHIKV-fed mosquitoes were able to transmit virus, and induce viraemia in, 3/3 Irf3/7 −/− mice via mosquito bites. In contrast, 0/3 Irf3/7 −/− mice became infected after bites from VLA1553-fed mosquitoes. RT-qPCR comparisons with phase 1 clinical data for VLA1553-vaccinated individuals indicated that VLA1553 viraemia was at or below the aforementioned threshold for transmission. Conclusions The evidence presented herein argue that the low viraemia in VLA1553-vaccinated individuals would mitigate against transmission. In addition, replication of VLA1553 in mosquito bodies was also significantly attenuated. Overall, mosquito-borne transmission of VLA1553 from vaccinated individuals to others appears improbable. Graphical Abstract